Analisis Dampak Limbah Home Industri Tokek Terhadap Lingkungan Berdasarkan Ketentuaan Hukum Lingkungan Dusun Banjar Anyar - Aura Devi Hernanda; Nur Qoilun (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
This study aims to analyze the environmental impact of waste generated by the gecko processing home industry based on environmental law regulations in Indonesia. In its processing activities such as lizards and snakes. These activities produce organic waste in the form of animal organs, blood, body fluids, and other waste in the materials that are later utilized as catfish feed. The research method used is qualitative with a normative juridical approach, statutory approach, and literature study. Data were obtained from laws and regulations , scientific journal, and environmental law literature. The results of the study indicate that the disposal of waste into rivers can increase Biological Oxyen Demand and Chemical Oxygen Demand (COD) levels, cause unpleassant odors, and reduce water quality and public health. The utilization of waste as catfish feed can reduce the amount of waste disposed of, however, it still requires hygienic processing to prevent biological risks. From the perspective of environmental law, the direc disposal of the waste into rivers is not in accordance with Law No. 32 of 2009 concerning Environmental Protection and Management and Government Regulation No. 22 of 2021 concerning the Implementation of Environmental Protection and Management. Therefore, better waste management is needed through proper waste treatment, increased awareness among business actors, and goverment supervision so that home industries can operate sustainably and in an environmentally friendly manner